2017
DOI: 10.1007/s12664-017-0768-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of platelet-lymphocyte ratio and CA 19-9 in differentiating benign from malignant head masses in patients with chronic pancreatitis

Abstract: PLR may be useful to differentiate PDAC from benign IHM in patients with chronic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Consistent with the results of the previous study, the present study demonstrated that LMR possessed important prognostic information for PDAC and was associated with poor OS. According to studies by Kakkat et al (27) and Asari et al (28), high pre-treatment PLR is an independent predictive risk factor for patients with PDAC, which was not demonstrated in the present study. In addition, the majority of the patients received chemotherapy, but the effect of chemotherapy on overall survival was not investigated; the effect of chemotherapy on the statistical importance of NLR and PLR in OS needs to be further explored in the future.…”
Section: Discussioncontrasting
confidence: 89%
“…Consistent with the results of the previous study, the present study demonstrated that LMR possessed important prognostic information for PDAC and was associated with poor OS. According to studies by Kakkat et al (27) and Asari et al (28), high pre-treatment PLR is an independent predictive risk factor for patients with PDAC, which was not demonstrated in the present study. In addition, the majority of the patients received chemotherapy, but the effect of chemotherapy on overall survival was not investigated; the effect of chemotherapy on the statistical importance of NLR and PLR in OS needs to be further explored in the future.…”
Section: Discussioncontrasting
confidence: 89%
“…Persistence of the inflammatory process within the tumor leads to an increase in the proliferation of tumor cells, angiogenesis, and the inhibition of apoptosis [13,14]. Several reports have suggested that markers of systemic inflammation including cytokines, C-reactive protein, NLR, and PLR may provide useful information on the prognosis of colorectal gastrointestinal cancer [15,16]. Thus, pathogenesis of PAC appears to be an inflammation-driven malignancy, as well as colorectal gastrointestinal cancer.…”
Section: Inflammation and Pacmentioning
confidence: 99%
“…An increasing number of studies have shown that elevated PLT levels are associated with tumor cell growth and angiogenesis ( 20 ). For example, it was reported that the PLT count in pancreatic ductal adenocarcinoma (PDAC) patients was higher than that in CP patients with an inflammatory mass of the pancreatic head ( 21 ). Similarly, the level of PLT in PC patients in an early tumor-node-metastasis (TNM) stage (I, II) was significantly higher than that in healthy controls ( 22 ).…”
Section: Discussionmentioning
confidence: 99%